Implementasi Sanksi Hukum Bagi Pengguna Modifikasi Motor Knalpot Racing Berdasarkan Undang-Undang Nomor 22 Tahun 2009 Perspektif Fiqh Siyasah - Rima Oktaviani Fanidia; John Kenedi; Ismail Jalili (Journal of Sharia and Legal Science, 2024)
Law Number 22 of 2009 concerning Traffic and Road Transportation prohibits the use of racing motorcycle exhausts. However, people still often use them, especially teenagers. This occurs in various regions, including in the Bengkulu Regional Police Jurisdiction. Thus, the main problem of this research is how to implement legal sanctions for users of racing motorcycle exhaust modifications and what is the Fiqh Siyasah perspective on this. This type of research is field research, namely the object of research directly at the Traffic Directorate (Ditlantas) of the Bengkulu Regional Police using a qualitative approach. Based on the results of the study, it was concluded that legal sanctions for users of racing motorcycle exhaust modifications have been implemented based on Law Number 22 of 2009, but have not been optimal. The principles of Fiqh Siyasah such as public interest, justice, prevention, and government authority support this action, with the aim of protecting the safety and interests of the community. Effective law enforcement requires cooperation between the government and the community, the use of modern technology, and an educational approach, so that it is expected to create a safe, comfortable, and harmonious environment for all.